Tujuan Pendidikan Perspektif Hadis - Lubis, Zulfahmi; Handayani, Irma; Anwar, Wan Tasya; Hidayati, Yusranida; Fathimah, Laila (Universitas Pahlawan Tuanku Tambusai, 2024)
Aqidah This study aims to examine the concept of educational objectives from the perspective of the Prophet Muhammad's hadiths. Islamic education is strongly grounded in the Qur'an and Hadith, with the ultimate goal of developing insan kamil, a balanced individual in both physical and spiritual aspects. This research focuses on analyzing hadiths relevant to education, particularly regarding educational objectives in Islam. The methodology used in this study is a literature review with a descriptive-analytical approach to uncover the values embedded in the hadiths. The findings indicate that the hadiths provide comprehensive guidance on education, including character building, enhancing faith, and developing life skills. Additionally, the hadiths offer practical teaching methods such as dialogue, exemplary behavior, and moral reinforcement. This study underscores the importance of applying educational values derived from the hadiths in contemporary contexts to address modern challenges. Keywords: Educational Objectives, Hadith, Islamic Education, Insan Kamil, Islamic Values